Relation Between Hypertension and Cognitive Impairment in Elderly at Posyandu Lansia Developed by Puskesmas Ngoresan, Surakarta - Matius Dimas Reza Dana Ismaya; Ratna Kusumawati; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: Hypertension is a condition of increasing blood pressure and it causes certain symptoms which will further damage the body. Elderly or a person older than 60 years old will be more susceptible to hypertension because there were many changes in body function and structure. Hypertension will lead to changes in vascular structures, disruption of cerebral autoregulation, white matter lesion, lacunar infarction, and eventually result in cognitive impairment. This study aims to determine a relation of hypertension to cognitive impairment in elderly at Posyandu Lansia developed by Puskesmas Ngoresan, Surakarta and factors which affect cognitive impairment. Methods: This was an observational analytic research with a cross sectional study. This research was done in Posyandu Lansia and general clinic of Puskesmas Ngoresan, Surakarta. The subject of the research was the elderly with hypertension at Puskesmas Ngoresan, Surakarta, male, aged ? 60 years, and literate. The 60 samples were taken using purposive sampling technique, which consist of 30 with hypertension and 30 without hypertension. Blood pressure was measured by using mercury sphygmomanometer. The assesment of cognitive function was done by using the Indonesian version of Montreal Cognitive Assessment (MoCA-Ina). The data were analyzed using chi square and multiple logistic regression. Results: The result of analytic test between hypertension and cognitive impairment showed significant relation (OR = 7.59; CI 95% = 1.73 33.30; p = 0,007). There was significant relation between smoking activity and cognitive impairment (OR = 0.07; CI 95% = 0.01 0.40; p = 0.003). Level of education and hypertension duration showed non significant relation to cognitive impairment with each value is p = 0.059; p = 0.697. Conclusions: Hypertension is a factor that increases the risk of cognitive impairment and smoking is a factor that decreases the risk of cognitive impairment. Keywords: Cognitive Impairment, Hypertension